2016
DOI: 10.1016/j.advwatres.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Monte Carlo methods for computing failure probability of porous media flow systems

Abstract: Multilevel Monte Carlo methods for computing failure probability of porous media flow systems. Advances in Water Resources AbstractWe study improvements of the standard and multilevel Monte Carlo method for point evaluation of the cumulative distribution function (failure probability) applied to porous media two-phase flow simulations with uncertain permeability. To illustrate the methods, we study an injection scenario where we consider sweep efficiency of the injected phase as quantity of interest and seek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…23 However, MLMC has been shown to converge and perform well in numerous applications. 23,36,39,40 Another limitation is that the MLMC Theorem requires many constants to be known or approximated, 23 which adds the need for preliminary sampling when these constants are not available. However, the computational time for MLMC has been shown to be orders of magnitude less than for standard MC sampling, 22,23 which compensates for the time spent on preliminary sampling.…”
Section: Extension To Multiple Observablesmentioning
confidence: 99%
See 2 more Smart Citations
“…23 However, MLMC has been shown to converge and perform well in numerous applications. 23,36,39,40 Another limitation is that the MLMC Theorem requires many constants to be known or approximated, 23 which adds the need for preliminary sampling when these constants are not available. However, the computational time for MLMC has been shown to be orders of magnitude less than for standard MC sampling, 22,23 which compensates for the time spent on preliminary sampling.…”
Section: Extension To Multiple Observablesmentioning
confidence: 99%
“…The main limitation of the MLMC method is that the algorithm is heuristic and is not guaranteed to converge . However, MLMC has been shown to converge and perform well in numerous applications . Another limitation is that the MLMC Theorem requires many constants to be known or approximated, which adds the need for preliminary sampling when these constants are not available.…”
Section: Multilevel Monte Carlomentioning
confidence: 99%
See 1 more Smart Citation
“…Elsakout et al (2015) demonstrated the performance of MLMCMC for uncertainty quantification tasks involving reservoir simulation with less computational cost in comparison to the standard Markov Chain Monte Carlo method. Fagerlund et al (2016) combined selective refinement technique with the MLMC for estimating the sweep efficiency in a two-phase flow scenario where an absolute accuracy of failure probability in a magnitude 5 to 10 percent is required. Lu et al (2016) applied MLMC method for estimating cumulative distribution functions of QoI obtained from the numerical approximation of largescale stochastic subsurface simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The model hierarchy then often corresponds to different discretizations of the underlying PDE. There are extensions [11,12,13] of the multilevel Monte Carlo method [17,16] for rare event probability estimation, which are based on variance reduction with control variates, instead of importance sampling. The subset method [1,37] is another approach that has been extended to exploit a hierarchy of coarse-grid approximations in [35].…”
Section: Introductionmentioning
confidence: 99%